Green Infrastructure: Flood Control and Water Management - Demeterio, Rino Anthony; Velita, Lolita; Mayor, Alex; Flores, Jr., Januario (Future Science / FSH-PH Publications, 2023)
Water scarcity is a pressing issue in many parts of the world. One innovative solution to this problem is rainwater harvesting, which involves collecting and storing rainwater for later use. The study aims to install a rainwater harvesting and treatment system to :1. Reduce water loss by its running-off.2 Meeting the demands of increasing water. 3. Reducing groundwater contamination.4. Increase available water during dry season.5. Reduce flooding and potentially prevent flooding of roads. This is a descriptive research method and is purely qualitative. It used Focus Group Discussion (FGD), Interview, and secondary data to get the necessary information from three Consultants, three Executives, and four Professors who are experts in the field. The study found that the rainwater harvesting and treatment facility would be a feasible project. It would minimize water consumption costs and reduce flooding in the city, with potential for replication by other universities, governments, and private entities.